Role-Playing Model on Speaking Skill for Elementary School Students - Ristianisa, Lutfiana; Suhardi, Suhardi (Universitas Pendidikan Ganesha, 2021)
The lack of creativity and skills to speak Bahasa Indonesia in grade IV teachers in some elementary schools directly impacts the learning process of Bahasa Indonesia in the classroom. The learning process of Bahasa Indonesia lessons was still delivered with a mixture of mother tongue or daily regional language. The purpose of this study was to explore the significant influence of role-playing models on Indonesian language speaking skills in grade IV elementary school. This type of research was pseudo-experimental research (quasi-experimental) using a quantitative approach. The population in this study was the entire fourth grade of elementary school consisting of 7 elementary schools. The sampling process used the purposive sampling technique, which meant selecting experimental and control classes—the method of extracting data with field observations and live interviews. The results showed on the variable Indonesian language speaking skills; students obtained a value of Fcount was 81,352 and p = 0,000. So it can be concluded that there is a significant influence on applying role-playing type cooperative learning to the Bahasa speaking skills of grade IV elementary school students. The findings of this study will have implications for improving students' Bahasa speaking skills.